Enhancing Grade 1 Student Engagement in Mathematics through Learning Media at SDN Tanjung Jati 2 - Richa Artikasari; Nuril Mumtaz; Agung Setyawan; Kakoma Luneta (Yayasan Pondok Pesantren Nurul Islam Mojokerto, 2025)
The research aimed at enhancing student engagement in mathematics lessons at Class 1 of SDN Tanjung Jati 2 during the 2023/2024 academic year through the use of learning media. The subjects of the study were 12 students from Class 1 of SDN Tanjung Jati 2. The research employed both qualitative and quantitative analysis methods. The findings showed that in Cycle 1, student engagement reached 70%, while in Cycle 2, it increased to 85%. The increased engagement was reflected in several indicators, including students' attention to material explanations, their willingness to ask questions, their participation in listening to material explanations, and their readiness to complete tasks assigned by the teacher. This discovery indicates that the learning media used in the study successfully enhanced student engagement in mathematics lessons at Class 1 of SDN Tanjung Jati 2.